2016
DOI: 10.3389/fpls.2016.00542
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Proteomic Analysis of Two Barley Cultivars (Hordeum vulgare L.) with Contrasting Grain Protein Content

Abstract: Grain protein contents (GPCs) of barley seeds are significantly different between feed and malting barley cultivars. However, there is still no insight into the proteomic analysis of seed proteins between feed and malting barley cultivars. Also, the genetic control of barley GPC is still unclear. GPCs were measured between mature grains of Yangsimai 3 and Naso Nijo. A proteome profiling of differentially expressed protein was established by using a combination of 2-DE and tandem mass spectrometry. In total, 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 41 publications
2
23
0
1
Order By: Relevance
“…A group of intense spots of low molecular mass (6-21000 Da) and pI 4.5 of 5.5 (marked as a), were observed which corresponded to alpha-amylase/trypsin inhibitor proteins previously identified in developing barley seeds by Akagawa et al (Akagawa et al, 2007), Finnie et al (Finnie et al, 2002), Østergaard et al (Østergaard et al, 2004), Perrocheau et al (Perrocheau et al, 2005). A second group of alpha-amylase/trypsin inhibitor proteins have been previously identified with a low molecular weight range from 12-16000 Da and pI 5-7 (Bak-Jensen et al, 2004;Guo et al, 2016;) and could be the group of proteins highlighted between 12-21000 Da (marked as d, e). Perrocheau et al (Perrocheau et al, 2005) identified the hordeins and 12 S seed storage proteins, which were observed on both the pH 3-11 gel (marked as b) and 6-11 gels (marked as c) in the range of 35-45000 Da, in the pI 6-8 range.…”
Section: Barleymentioning
confidence: 74%
See 2 more Smart Citations
“…A group of intense spots of low molecular mass (6-21000 Da) and pI 4.5 of 5.5 (marked as a), were observed which corresponded to alpha-amylase/trypsin inhibitor proteins previously identified in developing barley seeds by Akagawa et al (Akagawa et al, 2007), Finnie et al (Finnie et al, 2002), Østergaard et al (Østergaard et al, 2004), Perrocheau et al (Perrocheau et al, 2005). A second group of alpha-amylase/trypsin inhibitor proteins have been previously identified with a low molecular weight range from 12-16000 Da and pI 5-7 (Bak-Jensen et al, 2004;Guo et al, 2016;) and could be the group of proteins highlighted between 12-21000 Da (marked as d, e). Perrocheau et al (Perrocheau et al, 2005) identified the hordeins and 12 S seed storage proteins, which were observed on both the pH 3-11 gel (marked as b) and 6-11 gels (marked as c) in the range of 35-45000 Da, in the pI 6-8 range.…”
Section: Barleymentioning
confidence: 74%
“…Then, focussing on the gluten fraction, as it is the major trigger for celiac disease, we separated proteins with a basic pI over a narrow pH range of pH 6-11. Putative identifications of proteins were obtained using current literature for each type of crop (Rocher et al, 1992;Varjonen et al, 1994;Rocher et al, 1996;James et al, 1997;Aalberse, 2000;Skylas et al, 2000;Finnie et al, 2002;Gellrich et al, 2003;Bak-Jensen et al, 2004;Østergaard et al, 2004;Perrocheau et al, 2005;Anderson and Wieser, 2006;Akagawa et al, 2007;Dupont et al, 2011;Londono et al, 2013;Vensel et al, 2014;Guo et al, 2016;Klubicová et al, 2016;Malalgoda and Simsek, 2017;Nałęcz et al, 2017;Zhou et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among cereals, barley ( Hordeum vulgare L.) is one of the oldest and most important cultivated crops, which ranks fourth in terms of production in the world (Guo et al . ). Furthermore, it is also well studied in terms of genetics, genomics and breeding and thus qualifies as a model plant for Triticeae research.…”
Section: Introductionmentioning
confidence: 97%
“…Proteomic analysis is a powerful approach that can provide qualitative and quantitative information of protein expression, which is invaluable in understanding the mechanisms involved in physiological processes [11]. This approach has been successfully used to provide new insights into the mechanisms underlying grain quality traits in cereals [12][13][14]. However, no such report is available for the grain amino acid content in rice.…”
Section: Introductionmentioning
confidence: 99%